Characterizations of Cr3+- doped SnO2 Powders Via a Hydrolysis Method - Loan, Trinh Thi; Hoang Huong, Vu (VNU Journal of Science: Mathematics - Physics; Vol 39 No 4DO - 10.25073/2588-1124/vnumap.4845, 2023)
In this work, the effect of annealing temperature and Cr 3+ concentration on the structural and optical properties of the SnO 2 host crystals has been investigated. The Cr-doped SnO 2 samples were synthesized by a simple hydrolysis method, using SnCl 4 .5H 2 O as the host precursor and CrCl 3 .6H 2 O as the source of dopant. X-ray diffraction and Raman scattering spectra analysis revealed a tetragonal rutile structure of Cr 3+ -doped SnO 2 samples. The Cr 3+  concentration and annealing temperature have no influence on the lattice parameters of the SnO 2  crystals, whereas affected the appearance and intensity of the Raman modes. The optical properties of the synthesized samples were explored by photoluminescence (PL) and photoluminescence excitation (PLE) analysis. Interestingly, besides the emission peaks related to the SnO 2 , emission transitions within Cr 3+ ions in the octahedral field of SnO 2 were observed.